Naringin inhibits lipopolysaccharide-induced activation of microglia cells - Bai, Jie; Li, Siyuan; Wu, Gang; Ma, Lei; Li, Chen; Liu, Hongtao; Zhang, Pengbo (Cellular and Molecular Biology, 2019)
The purpose of this study was to investigate the effect of naringin on lipopolysaccharide (LPS)-induced activation of BV2 microglia and inflammatory factor release, and the mechanism involved. Different concentrations of naringin were used to pretreat BV2 cells for 30 min, after which they were stimulated with 100 ng/mL LPS for different durations. The levels of NO, IL-1Î² and TNF-Î± in the cell culture medium was determined with ELISA and Griess method. The mRNA expressions of IL-1Î² and TNF-Î± was determined with RT-PCR. Changes in ERK and p65/NF-ÎºB signaling pathway proteins were assayed with Western blotting. After 12 h stimulation of BV2 cells with LPS, the levels of IL-1Î² and TNF-Î± in the cell culture medium were significantly increased, but naringin had no significant effect on these inflammatory factors. In the cells pretreated with naringin, LPS stimulated the activation of microglia to produce IL-1Î² and TNF-Î± in a dose-dependent manner. Naringin inhibited LPS-induced release of IL-1Î², to a certain extent. The TNF-Î± gene was overexpressed. In addition, LPS stimulated a dose-dependent decrease in NO production by BV2 after pretreatment with different concentrations of naringin. Naringin pretreatment of cells significantly inhibited the activation of p65/NF-ÎºB in a concentration-dependent manner. In BV2 microglia, naringin inhibits LPO-induced production of NO and inflammatory factors, through a mechanism involving inhibition of activation of the p65/NF-ÎºB signaling pathway.